An ontological framework for tele-monitoring in e-healthcare. (2016) - Das, Anupam; Saha, Arindita
Tele-monitoring is considered as a discipline that is meant to rehabilitate independent lifestyle in their place of stay, for persons suffering from different diseases and physical disabilities which forces them to get hospitalised (persons suffering from some chronical diseases, disabilities, which also includes the frail elderly). Adequately powered multicentre, randomised controlled trials are required to further evaluate the potential benefits and cost-effectiveness of tele-monitoring. This paper deals with a technically new ontological framework for tele-monitoring in e-healthcare which is cost effective and more efficient in nature.